Women and the Mafia. Opening up to history (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
In the editorial, the editor analyzes the relationship between the Mafia and women in the social sciences, tracing the contents and peculiarities of the contributions that appear in the monographic issue.